Qualidade das águas superficiais da área de influência das empresas de mineração MMX (ferro) e MPBA (ouro), na Região de Serra do Navio e Pedra Branca do Amaparí - AP - MELO, Carolina Rodrigues (2018)
The main goal of this study was to avaluate the quality of surface waters of the area influenced by the mining companies of iron and gold, in the area of Serra do Navio and Pedra Branca do Amaparí, state of Amapá, and to stablish the relationships between mining and environment. This study will contribute to the improvement of the population life quality, once the quality of the waters has a direct relationship with public health. For that, 16 samples of water were collected and analyzed from the small rivers William, Mário Cruz, Taboca, Jornal, Mata Fome, Taperebá and Silvestre. It could be interpreted, by the result of the analyses, that the mining companies had significant influence at the studied area, mainly in what concerns the color and turbidity values, since the extraction of the ores needs to remove the vegetable covering, resulting in an intense leaching process, responsible for a great amount of sediments to the water courses, reducing the penetration of the light, disabling the photosynthesis and harming the aquatic life, and decreasing the amount of fishes, base of the area population feeding. The element cyanide showed concentrations below 0,001 mg / L, what seams to point to a very efficient control by the MPBA Company toward the discard ore treated waters to the rivers. However, the cyanide should has been liberated to atmosphere in the gaseous form (HCN), leading serious environmental problems. That still needs more detailed study, mainly on the quantification of the concentrations liberated by the mining process, avoiding environmental problems that affect the area flora and fauna. Another important aspect was the high value of the pH in the sample collected in the confluence of William and Taboca rivers. This can facilitate the precipitation of toxic chemical elements as heavy metals and also effect nutrient solubility. For a better evaluation of the real influence of those mining companies toward the environment and the water resources, it is necessary to monitor the water quality during an entire water cycle with at least four sampling.